A coaching intervention using judo principles to reduce head impact in women's rugby union - Stodter, A.; Lillis, J.; McDonald, K. (The Arts and Sciences of Judo, 2023)
This case study used principles from judo for falling and landing to create and deliver a coaching intervention, aiming to promote safe and effective contact technique and reduce head impacts in women`s rugby union. Forty athletes and two coaches at a university club received the intervention, with eleven taking part in focus group and individual interviews evaluating their experiences. Results highlighted the distinct nature of women`s rugby culture, the importance of confidence in contact, supporting players` safety, and ways to progress coaching interventions for the benefit of the sport. This research can be used to inform future injury prevention strategies which incorporate cross-sport knowledge translation as well as athletes` and coaches` perspectives.